Prehospital End-tidal Carbon Dioxide Predicts Mortality in Trauma Patients. (4th March 2018) - Childress, Kelsey; Arnold, Kelly; Hunter, Christopher; Ralls, George; Papa, Linda; Silvestri, Salvatore
Abstract: Background : End-tidal carbon dioxide (EtCO2 ) measurement has been shown to have prognostic value in acute trauma. Objective : Evaluate the association of prehospital EtCO2 and in-hospital mortality in trauma patients and to assess its prognostic value when compared to traditional vital signs. Methods : Retrospective, cross-sectional study of patients transported by a single EMS agency to a level one trauma center. We evaluated initial out-of-hospital vital signs documented by EMS personnel including EtCO2, respiratory rate (RR), systolic BP (SBP), diastolic BP (DBP), pulse (P), and oxygen saturation (O2 ) and hospital data. The main outcome measure was mortality. Results : 135 trauma patients were included; 9 (7%) did not survive. The mean age of patients was 40 (SD17) [Range 16–89], 97 (72%) were male, 76 (56%) were admitted to the hospital and 15 (11%) went to the ICU. The mean EtCO2 level was 18 mmHg (95%CI 9–28) [Range 5–41] in non-survivors compared to 34 mmHg (95%CI 32–35) [Range 11–51] in survivors. The area under the ROC curve (AUC) for EtCO2 in predicting mortality was 0.84 (0.67–1.00) (p = 0.001), RR was 0.82 (0.63–1.00), SBP was 0.72 (0.49–0.96), DBP was 0.72 (0.47–0.97), pulse was 0.51 (0.26–0.76), and O2 was 0.64 (0.37–0.91). Cut-off values at 30 mmHg yielded sensitivity = 89% (51–99), specificity = 68% (59–76), PPV = 13% (6–24) and NPV = 99% (93–100) for predicting mortality. There was no correlation between RR and EtCO2 (correlation 0.16; p = 0.06). Conclusion : We found an inverse association between prehospital EtCO2 and mortality. This has implications for improving triage and assisting EMS in directing patients to an appropriate trauma center.